LARANGAN PENGUNAAN SARANA IBADAH SEBAGAI TEMPAT KAMPANYE POLITIK SESUAI DENGAN UNDANG-UNDANG NOMOR 7 TAHUN 2017 MENURUT FIQH SIYASAH - Nadia Putri Asarah; Nofialdi Nofialdi (Institut Agama Islam Negeri Batusangkar, 2022)
This study examines the prohibition of the use of religious facilities as a place for political campaigns in accordance with Law Number 7 of 2017 According to Fiqh siyasah. The problem in this thesis is the prohibition on the use of religious facilities as a place for political campaigns in accordance with Law number 7 of 2017 concerning elections according to fiqh siyasah. Research Objectives The type of research that the author uses in this research is library research with the documentation method. This type of research is carried out by collecting and reviewing existing data information with the help of references in the library such as books, similar previous research materials, articles and various notes and various journals through reading related to the problem under study. The results of the study show Law number 7 of 2017 concerning elections article 521 this prohibition is caused because there will be many impacts that will arise if the campaign is carried out in mosques, fearing slander and hate speech that will arise if carried out, there will be more things negative things that will arise if the campaign is carried out in places of worship. So it can be concluded that using the media of worship facilities that are intended or intended are mosques in Law Number 7 of 2017 in accordance with the Shari'a which is based on Q.S An-Nur verse 36 From the results of the study, it can be concluded that the harm obtained is greater than the benefits obtained from the mosque being used as a place for political campaigns, because the mosque must be free from slander and hate speech, not used to seek names or for personal gain. because there is more harm than benefit it can be concluded that Law Number 7 of 2017 does not conflict with siyasa fiqh.